Determinants of Midwife Performance on Antenatal Care in Surakarta and Karanganyar, Central Java - Titis Eka Gusti; Didik Tamtomo; Bhisma Murti (Journal of Health Policy and Management, 2018)
Background: A high maternal mortality rate is one of the major health problems in developing countries. Midwives have an important role to reduce maternal mortality rate by looking after a pregnant women and her baby throughout a phase of antenatal care, during labor and birth, and for up to 28 days after the baby has been born. The WHO Expert Committee on Midwifery stated that the competence of the midwife must extend beyond the provision of service at the time of delivery to total antenatal and postnatal care. This study aimed to examine the determinants of midwife performance on antenatal care in Surakarta and Karanganyar, Central Java.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at 25 community health centers in Surakarta and Karanganyar, Central Java, from April to May 2018. A total sample of 200 midwives was selected by simple random sampling. The dependent variable was midwife performance. The independent variables at level 1 of multilevel modeling (MLM) were age, tenure, motivation, knowledge, training, facility, and leadership. Community health center (Puskesmas) was taken as level 2 in the MLM. The data were collected by questionnaire and analyzed by MLM.Results: Longer tenure (b= 1.57; 95% CI= 0.11 to 3.02; p=0.035), provision of training (b=1.92; 95% CI= 0.45 to 3.40; p=0.011), high motivation (b=1.48; 95% CI =-0.13 to 3.09; p=0.072), better knowledge (b=1.61; 95% CI= 0.03 to 3.19; p=0.046), facility (b=1.44; 95% CI= 0.14 to 2.73; p=0.030), strong leadership (b=1.66; 95% CI= 0.18 to 3.13; p=0.028), and age ?27 years (b=2.08; 95% CI= 0.04 to 4.12; p=0.046) were positively associated with better performance of midwives. A large portion of variation in midwives performance was determined at Puskesmas level with ICC= 45.78%.Conclusion: Longer tenure, provision of training, high motivation, better knowledge, facility, strong leadership, and age ?27 years are positively associated with better performance of midwives. Community health center has an important contextual effect on midwife performance.Keywords: midwife, performance, age, tenure, motivation, training, leadership, community health centerCorrespondence: